OPTIMIZING SCHOOL LIBRARY PROGRAMS TO NURTURE LEARNERS’ ENTERPRENEURAL SKILLS - Rini Silvana; Evi Sofiah (Madaris: Jurnal Guru Inovatif, 2021)
Entrepreneurship in school has long been a great interest and considered essential to improve school quality based on 8 (eight) national education standards. However, programs of entrepreneurship in schools generally focus more on business rather than entrepreneurial skills such as creativity, risk-taking and managing projects and problem solving. Here, this study aimed to describe the strategy used to start entrepreneurship in school of MAN 1 Kota Tangerang through its school library. School library programs -when carefully designed- support learners’ needs, provide resources, foster critical thinking as well as nurture creativity of learners. Using qualitative research method with a case study approach, this study involved the head of school library, the school stakeholders and group of learners participating in the entrepreneurship programs. The data were collected through interviews, observations, and other relevant sources. The data analysis technique referred to the Interactive Model of Miles, Huberman, and Saldana which includes data collection, data condensation, data display, and conclusion. The findings showed school library initiatives were conceivably promising activities to help promote learners’ entrepreneurial skills.